2013
DOI: 10.1093/jxb/ert215
|View full text |Cite
|
Sign up to set email alerts
|

MAP65-1a positively regulates H2O2 amplification and enhances brassinosteroid-induced antioxidant defence in maize

Abstract: Brassinosteroid (BR)-induced antioxidant defence has been shown to enhance stress tolerance. In this study, the role of the maize 65kDa microtubule-associated protein (MAP65), ZmMAP65-1a, in BR-induced antioxidant defence was investigated. Treatment with BR increased the expression of ZmMAP65-1a in maize (Zea mays) leaves and mesophyll protoplasts. Transient expression and RNA interference silencing of ZmMAP65-1a in mesophyll protoplasts further revealed that ZmMAP65-1a is required for the BR-induced increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 67 publications
0
20
0
1
Order By: Relevance
“…For instance, both ROS‐induced microtubule depolymerization (Yao et al ) and MTs‐resulted ROS accumulation (Wang et al ) were reported in the previous studies. In addition, Zhu et al () demonstrated a positive H 2 O 2 amplification loop regulated by MAP65, a microtubule‐associated protein. However, no information is available on the relationship between ROS and MTs in guard cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, both ROS‐induced microtubule depolymerization (Yao et al ) and MTs‐resulted ROS accumulation (Wang et al ) were reported in the previous studies. In addition, Zhu et al () demonstrated a positive H 2 O 2 amplification loop regulated by MAP65, a microtubule‐associated protein. However, no information is available on the relationship between ROS and MTs in guard cells.…”
Section: Discussionmentioning
confidence: 99%
“…ANPs are required during cytokinesis, but also regulate pavement cell expansion, since anp2anp3 mutants show aberrant epidermal cell morphology (Beck et al, 2010). Notably, downstream the MAPK cascade act two conserved key regulators of cortical MT array organization, the microtubule-associated proteins MAP65-1 and MAP65-2, which both have been implicated in ROS responses (Lucas et al, 2011;Zhu et al, 2013;Livanos et al, 2012). Potentially, H 2 O 2 sensed by the ANP cascade modulates cytoskeleton dynamics during cell proliferation and expansion (Fig.…”
Section: Ros and The Regulation Of The Cytoskeleton And Vesicle Transmentioning
confidence: 99%
“…ZmMAP65-1a that was found to be increased after application of hydrogen peroxide was also shown to regulate hydrogen peroxide amplification upon treatment of Zea mays leaves with brassinosteroid phytohormones. 33 The ROSresponsive ZmMPK5 interacts with ZmMAP65-1a toward activating the expression of NADPH oxidase genes and the subsequent responses. 33 In particular, the transcription of several antioxidant defense genes, which is initiated after NADPH oxidase activation, requires the phosphorylation of ZmMAP65-1a by ZmMPK5.…”
Section: Implications Of Cytoskeletal Contribution To Deliberate Ros mentioning
confidence: 99%
“…33 The ROSresponsive ZmMPK5 interacts with ZmMAP65-1a toward activating the expression of NADPH oxidase genes and the subsequent responses. 33 In particular, the transcription of several antioxidant defense genes, which is initiated after NADPH oxidase activation, requires the phosphorylation of ZmMAP65-1a by ZmMPK5. 33,34 Therefore, it is very interesting that, during stress, cytoskeletal proteins respond to elevated ROS levels and at the same time activate the NADPH oxidase assisting the purposeful production of ROS.…”
Section: Implications Of Cytoskeletal Contribution To Deliberate Ros mentioning
confidence: 99%
See 1 more Smart Citation